2020
DOI: 10.4067/s0717-75182020000100057
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and nutritional aspects of babassu coconut almond and oil (Orbignya phalerata Mart.)

Abstract: The potential use of babassu (Orbignya phalerata Mart.) in several activities is large. In view of these facts, this study aimed to determine the physicochemical composition of the babassu almond (OpAM) and evaluate the chemical, physical and physicochemical aspects of babassu coconut oil isolated by different methods of extraction. Babassu nut oil was removed by extraction with a hot solvent (Soxhlet) (OpS), hydraulic pressure (OpHP) and cold extraction (Blight and Dyer) (OpBD). Two artisanal samples from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Table 4 shows the chemical composition of BKO extracted by UAE and Soxhlet extraction. As can be seen in this table, the extraction method did not affect the fatty acid profile of BKO which is mainly composed of lauric acid and myristic acid responsible for the highly saturated composition of the oil (~86%), as already reported (Costa et al, 2020; Ferrari & Soler, 2015). Lauric acid is commonly found in coconut oil and its intake is associated with health benefits such as anticancer effects (Lappano et al, 2017) and anti‐inflammatory (Nishimura et al, 2018), in addition to having anti‐microbial properties (Dayrit, 2015), which enhances the application of this oil in the food and pharmaceutical industries.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Table 4 shows the chemical composition of BKO extracted by UAE and Soxhlet extraction. As can be seen in this table, the extraction method did not affect the fatty acid profile of BKO which is mainly composed of lauric acid and myristic acid responsible for the highly saturated composition of the oil (~86%), as already reported (Costa et al, 2020; Ferrari & Soler, 2015). Lauric acid is commonly found in coconut oil and its intake is associated with health benefits such as anticancer effects (Lappano et al, 2017) and anti‐inflammatory (Nishimura et al, 2018), in addition to having anti‐microbial properties (Dayrit, 2015), which enhances the application of this oil in the food and pharmaceutical industries.…”
Section: Resultssupporting
confidence: 81%
“…The higher yield of Soxhlet extraction can be attributed to the extraction of non-lipid compounds such as waxes and unsaponifiable materials (Özcan et al, 2019), due to the long period of contact with the heated solvent. The Y o obtained in these studies is in accordance with the values reported in the literature for babassu kernel, which vary from ~49.5% to ~60% (Costa et al, 2020;Oliveira, Mazzali, et al, 2019;Ramirez-Niño et al, 2018;Santos et al, 2013;Souza et al, 2019Souza et al, , 2021.…”
Section: Oil Yieldsupporting
confidence: 90%
See 2 more Smart Citations
“…[ 6 ] Babassu is considered the world's largest source of wild nut oil, accounting for 60–72% weight of the kernel. [ 7 ] The industrial extraction of this oil generally involves a mechanical press and the use of solvents, generating ≈337 kg of waste for each ton of kernels used. [ 8 ] The waste generated is called BC, which is widely used for feeding ruminants in the region where it is produced.…”
Section: Introductionmentioning
confidence: 99%